2016
DOI: 10.4028/www.scientific.net/amm.836.271
|View full text |Cite
|
Sign up to set email alerts
|

Flame Stability Measurement on Rectangular Slot Meso-Scale Combustor

Abstract: The biggest problem of combustion in the micro-scale or meso-scale combustor is heat loss. Heat loss led to a difficult of stable flame. This research aims to elucidate the flame stabilization and flammability limit of LPG-oxygen premixed flame, temperature distribution and flame visualization. Flame stabilization and flammability limit map are shows in φ - U plane. The result shows that there are six regions in the map that is stable without noise, stable with noise, transition zone, dead zone, pseudo stable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The role of the flame holder is also very important in the process of flame stabilization. Several types of flame holders have been tried, including porous media [20], wire mesh [21], backward-facing step [22], and slit [23][24][25]. Turbulent intensity on Micro-Combustor with Slits on both sides of the Bluff Body (MCSB) is greater thus it prolongs residence time and increases combustion efficiency and velocity extinction limit [24].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The role of the flame holder is also very important in the process of flame stabilization. Several types of flame holders have been tried, including porous media [20], wire mesh [21], backward-facing step [22], and slit [23][24][25]. Turbulent intensity on Micro-Combustor with Slits on both sides of the Bluff Body (MCSB) is greater thus it prolongs residence time and increases combustion efficiency and velocity extinction limit [24].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It has been revealed from previous studies [15] that the use of pure oxygen produces a very high flame propagation speed, consequently the flame stability limit shifts to a rich mixture, this is due to the fact that the flame had a flashback at a low equivalent ratio. Improvement effort has been made to delay the occurrence of flashback by using a double narrow slit flame holder [16] which results showed that the flame stability limit can extend to the low equivalent ratio (lean mixture). However, the experiment was only carried out on the combustor with a single aspect ratio.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%